Hygienic Practices of Vendors and Their Contribution to Coliform, Salmonella, and Shigella Bacteria of Raw Milk at Asella Town, Oromia, Ethiopia - Hirpo Tusa; Tsegaye Alemayehu; Bereket Wake Subussa; Henok Ayalew; Musa Mohammed Ali (International Journal of Food Science)
Background. Coliform, Salmonella, and Shigella are among the most encountered bacteria in raw milk. This study is aimed at determining the extent of coliform, Salmonella, and Shigella bacteria in raw milk and vendor hygiene practices at Asella town, Oromia Regional State, Ethiopia, from March 1 to 30, 2022. Methods. In this study, 210 milk vendors were included; each vendor provided a 50 ml sample of raw milk. Bacteria were isolated and identified using standard bacteriological techniques. Data were entered and analyzed using EPI info version 7 and SPSS version 22, respectively. A binary logistic regression model was applied to determine the factors associated with bacterial contamination of raw milk. Results. The total contamination percentage of raw milk was 50 (23.8%) (95% CI: 18.1-29.5%). The predominant bacteria identified were coliform 43 (20.5%) followed by Salmonella species 7 (3.3%). Among coliforms, the predominant bacteria were Citrobacter species 15 (34.9%) followed by Enterobacter species 11 (25.6%), Escherichia coli and Serratia species each 6 (14%), and Klebsiella species 5 (11.6%). However, no Shigella was isolated in this study. Not having the habit of washing cow teats (p<0.0001), the habit of washing teats with tap water (p<0.0001), not having separate cloth during milking (p<0.0001), not having a practice of testing milk for bacterial contamination (p=0.027), and not having separate vending environment (p=0.039) were significantly associated with bacterial contamination of raw milk. Conclusions. The percentage of bacterial contamination of milk was found to be high. Participants without a habit of washing cow teats, a habit of washing milk utensils with only tap water, and not having separate vending environments were associated factors for bacterial contamination of raw milk. Milk vendors are advised to develop the habit of washing teats before milking, avoid washing teat/milk utensils only with tap water, and have a separate vending environment.